KAIDAH KEMUTTASILAN SANAD HADIS (Studi Kritis Terhadap Pendapat Syuhudi Ismail) - Syamsuddin, Sahiron (UIN Sunan Kalijaga Yogyakarta, 2014)
The study of the sanad is very important in hadith studies. This article attempts to analyze and criticize Syuhudi Ismail theory of the ittisal sanad (the connectedness of hadith chain). The author comes to two conclusions. First, a chain hadith is considered muttasil (unbroken) if each narrator to the previous nearest narrator validly existing under the provisions of tahammul wa 'al-ada’ al-hadis and according to historical provisions. Second, the credibility, religious commitment, and cleverty (siqah, ‘adalah, dâbit) are not something that are essential in determining ittisal sanad. The ‘adalah (religious commitment) (without cleverty) should be sufficient, as long as it does not fall on mudallis narrators category.